Building a Golden Generation Through Learning Islamic Religious Education: Quantum Teaching Learning Model - Muis, Muhammad Aufa; Mardiana, Mardiana; Syalini, Selly; Putri, Nurusyakira (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2024)
This article explores the Quantum Teaching approach as an effective learning model in teaching Islamic Religious Education (PAI) to build a golden generation. The aim is to examine the application of Quantum Teaching principles in the PAI teaching and learning process, including a conducive learning environment, meaningful learning experiences, and the cultivation of spiritual values. The method used is an in-depth literature study about Quantum Teaching and best practices in PAI learning. The findings show that Quantum Teaching provides a holistic framework for creating a fun, interactive and meaningful learning environment, thereby facilitating the optimal development of students' spiritual, emotional and intellectual intelligence. In conclusion, the application of Quantum Teaching in PAI learning has the potential to form a golden generation who is not only academically intelligent, but also has noble character and strong spiritual intelligence.